2011
DOI: 10.1371/journal.pone.0017857
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down Control of Herbivory by Birds and Bats in the Canopy of Temperate Broad-Leaved Oaks (Quercus robur)

Abstract: The intensive foraging of insectivorous birds and bats is well known to reduce the density of arboreal herbivorous arthropods but quantification of collateral leaf damage remains limited for temperate forest canopies.We conducted exclusion experiments with nets in the crowns of young and mature oaks, Quercus robur, in south and central Germany to investigate the extent to which aerial vertebrates reduce herbivory through predation. We repeatedly estimated leaf damage throughout the vegetation period.Exclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 66 publications
2
65
0
2
Order By: Relevance
“…The use of exclusion nets to determine the relative effects of predation by birds and bats on arthropods indicates that there is an equal or stronger effect of bats on arthropod abundance [80][82]. Moreover, bat predation of arthropods had an indirect effect on herbivory, providing a strong case for bats as biological agents of pest control [81], [82].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of exclusion nets to determine the relative effects of predation by birds and bats on arthropods indicates that there is an equal or stronger effect of bats on arthropod abundance [80][82]. Moreover, bat predation of arthropods had an indirect effect on herbivory, providing a strong case for bats as biological agents of pest control [81], [82].…”
Section: Discussionmentioning
confidence: 99%
“…The use of exclusion nets to determine the relative effects of predation by birds and bats on arthropods indicates that there is an equal or stronger effect of bats on arthropod abundance [80][82]. Moreover, bat predation of arthropods had an indirect effect on herbivory, providing a strong case for bats as biological agents of pest control [81], [82]. Thus, the high activity level and diversity of insectivorous bats we found around dense healthy assemblages of acacia trees and also in irrigated agriculture might indicate that bats act as a biological control agent in both natural and agricultural habitats in the Arava.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we found that parameters such as composition, abundance, and species richness respond to the interactions between species as depredation, competition, and mutualism. For example, it has been reported that arthropod communities associated to oak canopies respond to predation by natural enemies as birds (Gunnarsson and Hake 1999;Murakami and Nakano 2000;Barber and Marquis 2009;Böhm et al 2011;Schönrogge et al 2013;Ceia and Ramos 2014), bats (Böhm et al 2011), parasites, and parasitoids (Sanchez et al 2013), in terms of abundance. However, most the studies have evaluated the influence of birds as regulators of species populations that integrate the arthropod communities.…”
Section: Biotic Interactionsmentioning
confidence: 99%
“…In this context, it is important to note that we have just started to understand the ecological role bats fill in natural ecosystems. For example, bats have been recently documented as top-down regulators of insect populations in forest habitats of the tropics and temperate zone (Kalka et al 2008;Boehm et al 2011) and also in subtropical coffee and cacao plantations (Williams-Guillen et al 2008;Maas et al 2013). Finally, bats are protected by law in some countries.…”
Section: Why Care About Bat Conservation?mentioning
confidence: 99%